A novel instrumented walker for individualized visual cue setting for gait training in patients with Parkinson's disease. Issue 4 (3rd July 2020) - Wu, Hsiao-Kuan; Chen, Huang-Ren; Chen, Wei-Ying; Lu, Chia-Feng; Tsai, Mei-Wun; Yu, Chung-Huang
ABSTRACT: Patients with Parkinson's disease suffer from gait disturbances, such as a shuffling and festinating gait, which reduces their quality of life. To circumvent this problem, external visual cues may be applied in gait training to maintain the integrity of motor function. However, conventional training methods, such as transverse lines stuck on the ground, are difficult to adjust and adapt to personalized gait ability. This study proposes a convenient instrumented wheel walker that provides gap adjustable visual cues and selectable projection modes onto the ground with and without motion relative to the user. Ten subjects with Parkinson's disease were recruited, and the efficacy of the proposed device for their gait training was assessed. We demonstrated the applicability of our device to address personalized demands in gait guidance. With a personalized setting for patients with Parkinson's disease, a significantly lengthened stride length may be achieved.